ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO TUTORIAL - Yeka Hendriyani; Vera Irma Delianti; Lativa Mursyida (Universitas Negeri Padang, 2018)
The purpose of this article is to analyze the need for developing video tutorials at Data Mining. This research is descriptive exploratory research. The subjects of this study were students of the Information Engineering Education Study Program in the Electronics Engineering Department, Faculty of Engineering, Universitas Negeri Padang, 2016. Samples were randomly selected as many as 30 students. Data was collected using observation sheets in the lecture process of Data Mining and student questionnaires. The results of the observation show that the learning material in the Data Mining course is in the form of presentation slides/power points and handbooks/texts both face to face and e-learning. The results of the needs questionnaire analysis show that students need learning media that can guide them to be able to learn independently by repeating lessons anytime and anywhere in the form of learning media in the form of video tutorials.